Práticas de gestão do uso da energia e sua relação com o desempenho sustentável no setor mineral brasileiro - Perlin, Ana Paula (2016)
Energy is an essential commodity for the existence of industrial activities, however the lack of management of energy use can lead to numerous environmental, economic and social. Thus industries as energy-intensive play an essential role in the search of the preservation of the energy system. This study aimed to analyze the energy use management practices and its relationship to sustainable performance in the industries of the Brazilian mineral sector. Energy use management practices were measured by the model proposed by Liu et al. (2012). Next, the sustainable performance was identified from the performance indicators developed by the Global Reporting Initiative - GRI (2006, 2010b, 2014). The study is characterized as quantitative and was conducted from conducting a survey research with industries linked to the Brazilian Mining Institute. It was found that the practices regarding the use of existing energy management in companies are related to periodic verification of the impacts of their activities on the environment and encouraging daily energy-saving practices. By contrast the energy use management practices still not widespread in companies are adopting the ISO 50001 and the existence of an Internal Commission for Energy Conservation (CICE). Overall, from the analyzes performed it can be seen that there are positive associations between factors related to energy use management practices and sustainable performance. Thus, it was identified that management practices of energy use involving the integration of energy efficiency in organizations and monitoring of energy use management relate directly to the performance of enterprises, in social, economic and environmental terms.